Motor responses to a steady beat. (March 2015) - Schaefer, Rebecca S.; Overy, Katie
Abstract : It is increasingly well established that music containing an isochronous pulse elicits motor responses at the levels of both brain and behavior. Such motor responses are often used in pedagogical and clinical practice to induce movement, particularly where motor functions are impaired. However, the complex nature of such apparently universal human responses has, arguably, not received adequate research attention to date. In particular, it should be noted that many adults, including those with disabilities, find it somewhat difficult to synchronize their movements with a beat with perfect accuracy; indeed, perfecting the skill of being musically "in time" can take years of training during childhood. Further research is needed on the nature of both the specificity and range of motor responses that can arise from the perception of a steady auditory pulse, with different populations, musical stimuli, conditions, and required levels of accuracy in order to better understand and capture the potential value of the musical beat as a pedagogical and therapeutic tool.